2016
DOI: 10.1002/tcr.201600062
|View full text |Cite
|
Sign up to set email alerts
|

Adaptable P–X Biaryl Phosphite/Phosphoroamidite‐Containing Ligands for Asymmetric Hydrogenation and C–X Bond‐Forming Reactions: Ligand Libraries with Exceptionally Wide Substrate Scope

Abstract: In this personal review, we present our efforts in the design of ligand libraries for the discovery of suitable metal catalysts for asymmetric hydrogenation and C-X bond-forming reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 161 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…Moreover, as Diéguez and coworkers have shown, the flexibility of tropos ligands has proven beneficial for a variety of Pd-catalyzed allylic substitutions because the flexible backbone can accommodate both hindered and unhindered substrates. 18,19 They have shown that phosphite, phosphonite, and phosphite-thioether tropos ligands are quite effective. 18, 19c For example, phosphite-oxazoline tropos ligands such as 2 were developed for the allylic substitution of three sterically different substrate classes including 3–5 (Scheme 3a).…”
Section: Tropos Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as Diéguez and coworkers have shown, the flexibility of tropos ligands has proven beneficial for a variety of Pd-catalyzed allylic substitutions because the flexible backbone can accommodate both hindered and unhindered substrates. 18,19 They have shown that phosphite, phosphonite, and phosphite-thioether tropos ligands are quite effective. 18, 19c For example, phosphite-oxazoline tropos ligands such as 2 were developed for the allylic substitution of three sterically different substrate classes including 3–5 (Scheme 3a).…”
Section: Tropos Ligandsmentioning
confidence: 99%
“…18,19 They have shown that phosphite, phosphonite, and phosphite-thioether tropos ligands are quite effective. 18, 19c For example, phosphite-oxazoline tropos ligands such as 2 were developed for the allylic substitution of three sterically different substrate classes including 3–5 (Scheme 3a). 20 Beyond the fact that the use of phosphite ligands increases reaction rates over phosphines, the flexible biphenyl backbone of the ligand increases catalyst adaptability.…”
Section: Tropos Ligandsmentioning
confidence: 99%
“…We and others have shown the benefits of having biaryl phosphite moieties in the ligands for several asymmetric catalytic transformations ,. Our group has contributed with an improved generation of phosphite‐N ligand libraries . In this context, we found that replacing the phosphine moiety in phosphine‐oxazoline PHOX ligands by a biaryl phosphite moiety not only improved activity but also increased substantially the substrate scope in the Pd‐allylic substitution and the Ir‐catalyzed hydroboration .…”
Section: Introductionmentioning
confidence: 82%
“…Our group has expertise in preparing easy to handle ligand families from readily available starting materials . We and others have shown the benefits of having biaryl phosphite moieties in the ligands for several asymmetric catalytic transformations ,. Our group has contributed with an improved generation of phosphite‐N ligand libraries .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation